Processes of local alcohol policy-making in England: Does the theory of policy transfer provide useful insights into public health decision-making?. (May 2019) - Gavens, Lucy; Holmes, John; Buykx, Penny; de Vocht, Frank; Egan, Matt; Grace, Daniel; Lock, Karen; Mooney, John D.; Brennan, Alan
Abstract: Background and aims: Recent years have seen a rise in new and innovative policies to reduce alcohol consumption and related harm in England, which can be implemented by local, as opposed to national, policy-makers. The aim of this paper is to explore the processes that underpin the adoption of these alcohol policies within local authorities. In particular, it aims to assess whether the concept of policy transfer (i.e. a process through which knowledge about policies in one place is used in the development of policies in another time or place) provides a useful model for understanding local alcohol policy-making. Methods: Qualitative data generated through in-depth interviews and focus groups from five case study sites across England were used to explore stakeholder experiences of alcohol policy transfer between local authorities. The purposive sample of policy actors included representatives from the police, trading standards, public health, licensing, and commissioning. Thematic analysis was used inductively to identify key features in the data. Results: Themes from the policy transfer literature identified in the data were: policy copying, emulating, hybridization, and inspiration . Participants described a multitude of ways in which learning was shared between places, ranging from formal academic evaluation to opportunistic conversations in informal settings. Participants also described facilitators and constraints to policy transfer, such as the historical policy context and the local cultural, economic, and bureaucratic context, which influenced whether or not a policy that was perceived to work in one place might be transferred successfully to another context. Conclusions: Theories of policy transfer provide a promising framework for characterising processes of local alcohol policy-making in England, extending beyond debates regarding evidence-informed policy to account for a much wider range of considerations. Applying a policy transfer lens enables us to move beyond simple (but still important) questions of what is supported by 'robust' research evidence by paying greater attention to how policy making is carried out in practice and the multiple methods by which policies diffuse across jurisdictions. Highlights: Policy transfer (PT) can aid understanding of how policies diffuse across places. PT is a useful framework for characterising local alcohol policy-making processes. PT acknowledges that a wide range of considerations inform policy debates.